2013
DOI: 10.4238/2013.january.30.9
|View full text |Cite
|
Sign up to set email alerts
|

Association of T1740C polymorphism of L-FABP with meat quality traits in Junmu No. 1 white swine

Abstract: ABSTRACT. This study was designed to investigate a single nucleotide polymorphism in intron 1 of the liver fatty acid-binding protein (L-FABP) gene in 156 Junmu No. 1 white swine using PCRsingle-strand conformational polymorphism. The association between the polymorphism and meat quality traits was also studied. The cloning and sequencing results indicated that the polymorphism in intron 1 was due to a T→C mutation at position 1740 of L-FABP, yielding three genotypes (TT, TC, and CC). Association analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The autogenous variation of H-FABP has an important influence on IMF deposition and other biological traits of chickens [ 24 ]. The assay of PCR-SSCP had been used to analyze polymorphisms for cows [ 37 ], pigs [ 38 ] and chickens [ 39 ]. Ye et al [ 40 ] assessed a SNP (C2054T) in the second intron of the Beijing-Oil chicken H-FABP gene that remarkably correlated with the IMF contents in the chest and leg muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The autogenous variation of H-FABP has an important influence on IMF deposition and other biological traits of chickens [ 24 ]. The assay of PCR-SSCP had been used to analyze polymorphisms for cows [ 37 ], pigs [ 38 ] and chickens [ 39 ]. Ye et al [ 40 ] assessed a SNP (C2054T) in the second intron of the Beijing-Oil chicken H-FABP gene that remarkably correlated with the IMF contents in the chest and leg muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of the A-FABP gene are found to be prognostic biomarkers in patients with acute coronary syndrome (Reiser et al, 2015) and type 2 diabetes mellitus (Alqahtani et al, 2016). They are usually researched as candidate genes that affect the deposition of intramuscular fat in pigs (Zhang et al, 2013), cattle (Jurie et al, 2007), chickens (Zhou et al, 2018), ducks (Saez et al, 2009), goats (Wang, Geng, Ji, & Chang, 2012) and sheep (Wang et al, 2014). The adipocyte fatty acid-binding protein (A-FABP) in the superfamily of lipid-binding proteins (Wang et al, 2006) plays an important role in the lipid deposition of muscles and homeostasis in adipocytes (Migdał et al, 2018).…”
mentioning
confidence: 99%
“…L-FABP polymorphisms were reported to be related to fatty acid such as C16:0, C18:3, and total IMF in chest muscle, where CC genotype had higher contents when compared to CT and TT genotypes (He et al, 2011). The effect on marbling in white swine showed that the polymorphism had a significant effect in genotype CC where it had more marbling than TC, and TC had more marbling than TT; besides, the effect on intramuscular fat content was also polymorphic, it showed that L-FABP might be a candidate gene associated with meat quality traits (Zhang et al, 2013). However, this gene and its effect on the quality of duck carcasses has never been explored in Indonesian local ducks.…”
Section: Introductionmentioning
confidence: 93%